The Association Between Heart Rate Variability and 90-Day Prognosis in Patients With Transient Ischemic Attack and Minor Stroke - Li, Changhong; Meng, Xia; Pan, Yuesong; Li, Zixiao; Wang, Mengxing; Wang, Yongjun (Frontiers in Neurology, 2021)
Background: Low heart rate variability (HRV) is known to be associated with increased all-cause, cardiovascular, and cerebrovascular mortality but its association with clinical outcomes in patients with transient ischemic attack (TIA) or minor stroke is unclear. Methods: We selected TIA and minor stroke patients. From each continuous electrocardiograph (ECG) record, each QRS complex was detected and normal-to-normal (N-N) intervals were determined. The standard deviation of all N-N intervals (SDNN) and the square root of the mean squared differences of successive N-N intervals (RMSSD) were calculated. Logistic regression analysis and Cox regression analysis were performed to assess the outcomes of patients at 90 days, and the odds and risk ratios (OR/HR) of each index quartile were compared. Results: Compared with SDNN patients in the lowest quartile, neurological disability was significantly reduced in other quartile groups at 90 days, with significant differences (OR of group Q2 was 0.659; 95% confidence interval [CI], 0.482-0.900; p=0.0088; OR of group Q3 was 0.662; 95% CI, 0.478-0.916; p=0.0127; OR of group Q4 was 0.441; 95% CI, 0.305-0.639; p <0.0001). Compared with the lowest quartile, the recurrence rate of TIA or minor stroke in patients of the two higher quartiles (Q3 and Q4) of SDNN was significantly reduced at 90 days (HR of Q3 group was 0.732; 95% CI, 0.539-0.995; p=0.0461; HR of Q4 group was 0.528; 95% CI, 0.374-0.745; p=0.0003). Conclusions: Based on our findings, autonomic dysfunction is an adverse indicator for neurological function prognosis and stroke recurrence 90 days after TIA or minor stroke.